ANALISIS RASIO LIKUIDITAS DALAM MEMENUHI KEWAJIBAN PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sintiya Bahi; Ilyas Lamuda; Novaliastuti Masiaga (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The objective of this research is to analyze the liquidity ratio in measuring the company's ability to meet obligations in trading companies listed on the Indonesia Stock Exchange. The usefulness of the research results is expected to contribute to the understanding of solving issues related to the analysis of factors affecting customer loyalty and can be used as a consideration for the companies studied in taking corrective steps for the future. It can also be used as an evaluation material in determining future company strategies. Financial ratio analysis is a part of business or risk prospect analysis for decision-making purposes by evaluating the business environment, strategy, and the company's financial position and performance. The financial statement analyses commonly used by companies include liquidity analysis, solvency analysis, and profitability analysis. Liquidity analysis provides insights into a company's ability to match short-term liabilities maturing with current assets. The liquidity ratio owned by the company can be used as an evaluation material and for the effectiveness of company management. Based on these issues, the author conducted research on "Liquidity Ratio Analysis in Meeting Obligations in Trading Companies Listed on the Indonesia Stock Exchange" using annual financial reports for the period 2020-2022. The data analysis technique in this study uses descriptive analysis by collecting data, classifying data, explaining, and analyzing to provide clear information and insights into the issues being researched. The results of the study show the liquidity ratio in measuring the ability of short-term debt of trading companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022, including PT. Bintang Oto Global Tbk, PT. Midi Utama Indonesia Tbk, PT. Wicaksana Overseas International Tbk, PT. Modern International Tbk, and PT. Perdana Bangun Pusaka Tbk. Viewed from the current ratio of 42.22% < 75%, it is categorized as unhealthy, meaning the hypothesis taken is that the company is unable to meet short-term debt obligations with the liquidity ratio. The quick ratio of 286.69% and the cash ratio of 181.31% > 150% are categorized as very healthy, thus the hypothesis taken is that the company is able to meet short-term debt obligations with the liquidity ratio.